Hierarchy of environmental factors driving restoration of dry grasslands: A multi‐site analysis. Issue 2 (12th April 2021) - Prach, Karel; Fajmon, Karel; Řehounková, Klára; Jongepierová, Ivana
Abstract: Questions: Quantification of the role of particular factors driving restoration may improve our understanding of restoration processes and thus lead to a better design of restoration projects. We investigated how restoration methods, soil characteristics, time since sowing or abandonment, proximity effects, and climate influence vegetation changes and restoration success in the restored grasslands. We particularly asked: (a) which of the studied environmental factors influence the course of restoration of dry grasslands and how much; (b) what is their hierarchy; and (c) what are the implications for ecological restoration? Location: White Carpathians Protected Landscape Area, eastern Czech Republic. Methods: We studied 82 dry grasslands restored on former arable land, either sown with a regional or commercial clover–grass seed mixture or left to spontaneous succession, and compared them with ancient dry grasslands as reference sites. Data were processed using Detrended Correspondence Analysis and Canonical Correspondence Analysis. Generalized linear models (GLMs) were used to test the relationships between two measures of restoration success (number of colonizing target species and Bray–Curtis similarity between restored and reference vegetation) and the environmental factors. Results: The ordination results demonstrate some convergence of grasslands restored with different methods toward reference sites. Using regional seed mixtures led to a higher participation of dry grassland species, while using commercial seed mixtures and spontaneous succession favored mesic grassland species. All tested groups of environmental variables exhibited some significant effects on the course of restoration. Their hierarchy varied depending on the vegetation characteristic we used but generally, restoration method and soil factors appeared to be the most important, followed by time since sowing or abandonment, climatic factors, and proximity effects. Conclusions: When planning grassland restoration projects, we have to consider especially soil characteristics and landscape context, i.e., location of the restored site in the landscape matrix and climatic conditions, and select proper restoration methods. Abstract : When planning grassland restoration projects, we have to consider especially soil characteristics and landscape context, and select proper restoration methods. Using regional seed mixtures led to a higher participation of target dry grassland species, while using commercial seed mixtures and spontaneous succession favored mesic grassland species.